PENGARUH STRES KERJA DAN WORK FAMILY CONFLICT TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH KEPUASAN KERJA PADA PT. TIRTA INVESTAMA - Muchamad Rafii Ar Rasid Mujahidin; Irmawati Irmawati (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the effect of work stress and work family conflict on employee performance mediated by job satisfaction at PT. Tirta Investama. This research method is quantitative. The population of this study is all employees of PT. Tirta Investama and the married. The sample size of this study was 150 respondents. This study used primary data. The sampling technique used in this study used nonprobability sampling. Data collection techniques in this study used questionnaires. Data analysis techniques used in this study with the help of SMARTPLS 3.0 software. The findings of this study state that Work Stress has a positive and significant influence on Employee Performance. Work Family Conflict has a positive and significant influence on Employee Performance. Work Stress has a positive and significant influence on Job Satisfaction. Work Family Conflict has a positive and significant influence on Job Satisfaction. Job Satisfaction has a positive and significant influence on Employee Performance. Job Stress has a positive and significant influence on Employee Performance mediated by Job Satisfaction. Work Family Conflict has a positive and significant influence on Employee Performance mediated by Job Satisfaction